2000
DOI: 10.1063/1.372363
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic properties of Fex–C1−x nanocomposite thin films

Abstract: Iron–carbon nanocomposite thin films with iron concentrations ranging from 12 to 74 at. % were grown by ion-beam sputtering codeposition at different substrate temperatures. The microstructure of the films was characterized by transmission electron microscopy, atomic force microscopy, extended x-ray absorption fine structure, and grazing incidence small-angle x-ray scattering. A granular morphology consisting of body-centered-cubic iron-rich nanoparticles (2–5 nm in diameter and 3–8 nm in height with a relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
65
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 54 publications
8
65
0
Order By: Relevance
“…The estimated value of K is of the same order as reported before for Fe-C nanoparticles ͑K ϳ 1.7 ϫ 10 7 ergs/ cm 3 ͒. 40 One distinction in the ZFC curve in Fig. 6 is a flat maximum located around 150± 30 K, indicating a broad particle size distribution after carbon SWNT growth.…”
Section: M/m S = Coth͑ H/k B T͒ − K B T/ H ͑2͒supporting
confidence: 65%
“…The estimated value of K is of the same order as reported before for Fe-C nanoparticles ͑K ϳ 1.7 ϫ 10 7 ergs/ cm 3 ͒. 40 One distinction in the ZFC curve in Fig. 6 is a flat maximum located around 150± 30 K, indicating a broad particle size distribution after carbon SWNT growth.…”
Section: M/m S = Coth͑ H/k B T͒ − K B T/ H ͑2͒supporting
confidence: 65%
“…Bubonneau et al have shown that in the related Fe-C system, the as-deposited films are composed of Fe nanoparticles embedded in a moreor-less graphitized C matrix. 12 It is known that the graphite phase ͑density of 2.2 g/cm 3 ) can transform into amorphous one ͑density of 1.6 g/cm 3 ) under thermal/laser treatment. 13,14 It is natural that this transformation is accompanied by the film thickness change.…”
mentioning
confidence: 99%
“…Saturation magnetization was very low 1 emu/gm. Results drawn for ferrites [1,2,6,7,10] and nanoparticles prepared by various method [8,9,11] were also found true for nano-Fe2O3 particles prepared by co-precipitation method. …”
Section: Introductionmentioning
confidence: 90%
“…Iron-rich nanoparticles of 2-8 nm were obtained. The saturation magnetization was found to decrease compared to the bulk value for pure α-Fe [9].Co-precipitation method was used to prepare Manganese ferrite, (MnFe2O4) fine particles in the size range 5-15 nm. The saturation magnetization again followed decreasing trend with decreasing size [10].…”
Section: Introductionmentioning
confidence: 99%